2006
DOI: 10.2298/mpns0604118p
|View full text |Cite
|
Sign up to set email alerts
|

The role of autonomic cardiovascular neuropathy in pathogenesis of ischemic heart disease in patients with diabetes mellitus

Abstract: Cardiovascular autonomic neuropathy is a common complication of diabetes that significantly correlates with coronary disease. Early diagnosis of cardiovascular autonomic neuropathy points to increased cardiovascular risk, providing a basis for preventive and therapeutic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Prasad et al studied cardiac autonomic dysfunction and ECG abnormalities in patients with Type II diabetes and found increased frequency of postural hypotension in patients with diabetes compared to healthy controls. Finding of the present study is in accordance with studies done by Jayabal et al [4] and Prasad et al [5] studies done in the past by Ewing et al, [6] Dyrberg et al, [7] Popovic et al, [8] Beylot et al, [9] and Barkai and Madacsy [10] had similar results. It can thus be concluded that the heart rate response to standing, a measure of cardiac parasympathetic function is reduced in uncontrolled diabetes patient groups compared to controls.…”
Section: Jayabal Et Al Studied Autonomic Function Test In Patients Withsupporting
confidence: 93%
“…Prasad et al studied cardiac autonomic dysfunction and ECG abnormalities in patients with Type II diabetes and found increased frequency of postural hypotension in patients with diabetes compared to healthy controls. Finding of the present study is in accordance with studies done by Jayabal et al [4] and Prasad et al [5] studies done in the past by Ewing et al, [6] Dyrberg et al, [7] Popovic et al, [8] Beylot et al, [9] and Barkai and Madacsy [10] had similar results. It can thus be concluded that the heart rate response to standing, a measure of cardiac parasympathetic function is reduced in uncontrolled diabetes patient groups compared to controls.…”
Section: Jayabal Et Al Studied Autonomic Function Test In Patients Withsupporting
confidence: 93%
“…genitourinary, and cardiovascular). The latter, diabetic cardiac autonomic neuropathy, is the most serious [12] and is a risk for heart disease [34], cardiovascular events [35] including silent myocardial infarction, stroke [36] and mortality [37].…”
Section: Plos Onementioning
confidence: 99%